Cardiomyocyte‐derived exosomal microRNA‐92a mediates post‐ischemic myofibroblast activation both in vitro and ex vivo. (25th January 2020) - Wang, Xujun; Morelli, Marco Bruno; Matarese, Alessandro; Sardu, Celestino; Santulli, Gaetano
Abstract: Aims: We hypothesize that specific microRNAs (miRNAs) within cardiomyocyte‐derived exosomes play a pivotal role in the phenoconversion of cardiac myofibroblasts following myocardial infarction (MI). Methods and results: We used an established murine model of MI, obtained in vivo via ligation of the left anterior descending coronary artery. We isolated adult cardiomyocytes and fibroblasts, and we assessed the functional role of cardiomyocyte‐derived exosomes and their molecular cargo in the activation of cardiac fibroblasts. We identified and biologically validated miR‐92a as a transcriptional regulator of mothers against DPP homologues 7 (SMAD7), a known inhibitor of α‐smooth muscle actin (α‐SMA), established marker of myofibroblast activation. We found that miR‐92a was significantly ( P < 0.05) upregulated in cardiomyocyte‐derived exosomes and in fibroblasts isolated after MI compared with SHAM conditions ( n ≥ 6/group). We tested the activation of myofibroblasts by measuring the expression levels of αSMA, periostin, and collagen. Primary isolated cardiac fibroblasts were activated both when incubated with cardiomyocyte‐derived exosomes isolated from ischemic cardiomyocytes and when cultured in conditioned medium of post‐MI cardiomyocytes, whereas no significant difference was observed following incubation with exosomes or medium from sham cardiomyocytes. These effects were attenuated when an inhibitor of exosome secretion, GW4869 (10 μM for 12 h) was included in the experimental setting. Through means of specific miR‐92a mimic and miR‐92a inhibitor, we also verified the mechanistic contribution of miR‐92a to the activation of cardiac fibroblasts. Conclusions: Our results indicate for the first time that miR‐92a is transferred to fibroblasts in form of exosomal cargo and is critical for cardiac myofibroblast activation.